UiTM Samarahan “Haunted Hospital” - Francis, Frannelya (Universiti Teknologi MARA, Sarawak, 2016)
The nursing students of UiTM Sarawak kick-started the new year 2016 with a creative and innovative project called the Haunted Hospital. This project was to raise funds for the upcoming nursing dinner, which is held annually. The Haunted Hospital project, which exposed the nursing students to entrepreneurship, was successfully held on 18 and 19 January 2016 from 6.00 pm to 10.30 pm in Blok E, Nursing Skills Laboratory.